Acute Respiratory Distress Syndrome: Current Concepts and Future Directions. Issue 4 (July 2013) - Fröhlich, S.; Murphy, N.; Ryan, D.; Boylan, J. F.
Acute respiratory distress syndrome is one of the leading causes of death in critically ill patients. Recent advances in supportive care have led to a moderate improvement in mortality. In particular, a much lower mortality rate than expected was evident in the severest category of patients (requiring extracorporeal membrane oxygenation) in Australia during the recent H1N1 pandemic. Though improvements in supportive care may have provided some benefit, there remains an absence of effective biological agents that are necessary to achieve further incremental reduction in mortality. This article will review the evidence available for current treatment strategies and discuss future research directions that may eventually improve outcomes in this important global disease.